How Significant Are Marine Invertebrate Collagens? Exploring Trends in Research and Innovation - Mariana Almeida; Tiago Silva; Runar Gjerp Solstad; Ana I. Lillebø; Ricardo Calado; Helena Vieira (Marine Drugs)
This review is focused on the research, innovation and technological breakthroughs on marine invertebrate collagens and their applications. The findings reveal that research dates back to the 1970s, and after a period of reduced activity, interest in collagens from several marine invertebrate groups was renewed around 2008, likely driven by the increased commercial interest in these biomolecules of marine origin. Research and development are predominantly reported from China and Japan, highlighting significant research interest in cnidarians (jellyfish), echinoderms (sea cucumbers, sea urchins and starfish), molluscs (squid and cuttlefish) and sponges. Co-word analysis of the literature highlights applications in regenerative medicine, the properties of hydrolysates, and biology and biochemistry studies. Innovation and the technological landscape, however, focus on fewer taxonomic groups, possibly reflecting the challenge of sustainably sourcing raw materials, with a higher number of patents coming from Asia. Globally, jellyfish collagen is the most prominent marine invertebrate source, while Asia also emphasizes the use of collagens derived from molluscs and sea cucumbers. Europe, despite fewer patents, explores a broader range of taxonomic groups. Globally, key applications registered are mostly in medical, dental and toiletry areas, with peptide preparations spanning multiple animal groups. The food domain is notably relevant for molluscs and sea cucumbers. Market trends show a strong presence of cosmetic and supplement products, aligning with market reports that predict a growing demand for marine collagens in cosmetics and personalized nutrition, particularly in targeted health supplements.